TRADE MODELS IN THE EUROPEAN UNION - Gräbner-Radkowitsch, Claudius; Tamesberger, Dennis; Heimberger, Philipp; Kapelari, Timo; Kapeller, Jakob (Economic Annals, 2022)
By studying the factors underlying differences in trade performance across European economies, this paper derives six different “trade models” for 22 EU countries and explores their developmental and distributional dynamics. We first introduce a typology of trade models by clustering countries on the basis of four key dimensions of trade performance: endowments, technological specialisation, labour market characteristics and regulatory requirements. The resulting clusters comprise countries that base their export success on similar trade models. Our results indicate the existence of six different trade models: the ‘primary goods model’ (Latvia, Estonia), the ‘finance model’ (Luxembourg), the ‘flexible labour market model’ (UK), the ‘periphery model’ (Greece, Portugal, Spain, Italy, France), the ‘industrial workbench model’ (Slovenia, Slovakia, Poland, Hungary, the Czech Republic), and the ‘hightech model’ (Sweden, Denmark, Netherlands, Belgium, Ireland, Finland, Germany and Austria). Subsequently, we provide a comparative analysis of the economic development and trends in inequality across these trade models. Inter alia, we observe a shrinking wage share and increasing personal income inequality in most of them, yet find that the ‘high-tech model’ is an exceptional case, being characterised by relatively stable economic development and an institutional setting that managed to counteract rising inequality.